Intestinal adenomas can develop with a stable karyotype and stable microsatellites - Haigis, Kevin M. (National Academy of Sciences, 2002)
Loss of function of the adenomatous polyposis coli (APC)/Apc tumor suppressor gene occurs early in the etiology of intestinal cancer in mammals. In human colonic tumors, genomic instability is proposed to be associated with tumor initiation by inducing loss of APC function. We have used a mouse model of inherited intestinal cancer (Apc(Min)/+, Min/+) to analyze the earliest stages of tumorigenesis in this organ. We find that tumors from C57BL/6 Min/+ mice have a stable karyotype and stable microsatellites. In contrast to previous claims, we find that homozygosity for the Min allele of Apc in tumors can proceed by homologous somatic recombination. Further, our analysis of early, benign human colorectal adenomas failed to reveal any evidence for generalized chromosomal or microsatellite instability. These results cast doubt on the hypothesis that either of these forms of genomic instability is necessary for the initial development of colorectal adenomas. We contrast our analysis of autochthonous primary tumors to other studies involving xenografts or cultured cells.